1993
DOI: 10.1111/j.1365-2125.1993.tb04219.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of orally deposited budesonide on the systemic availability of budesonide after inhalation from a Turbuhaler.

Abstract: 1 The aim of this pharmacokinetic study was to evaluate to what extent oropharyngeal deposition of drug contributes to the systemic availability of budesonide inhaled from a dry powder inhaler (Turbuhaler®). 2 The design was a randomized cross-over study in eight children aged 7-13 years. The plasma concentrations of the two epimers of budesonide (22R and 22S) after inhalation of 1 mg budesonide from a Turbuhaler were compared with the plasma concentrations obtained when the absorption of the drug deposited in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 12 publications
(16 reference statements)
1
15
0
2
Order By: Relevance
“…The should result in greater steady-state accumulation during repeated dosing. This is supported by a study where absorption of the same dose of budesonide was higher comparing turbuhaler with nebuhaler ( both without there was a large step-up in adrenal suppression between single and repeated doses of fluticasone 1000 mg twice charcoal ) being two-fold greater [ 25]. Allowing for greater oropharangeal deposition of budesonide with a daily (25% vs 55% suppression), whereas with budesonide 800 mg twice daily this effect was much less turbuhaler than with a nebuhaler, these data suggest an almost two-fold greater lung delivery of budesonide pronounced (26% vs 34% suppression) [32 ].…”
Section: Introductionmentioning
confidence: 78%
“…The should result in greater steady-state accumulation during repeated dosing. This is supported by a study where absorption of the same dose of budesonide was higher comparing turbuhaler with nebuhaler ( both without there was a large step-up in adrenal suppression between single and repeated doses of fluticasone 1000 mg twice charcoal ) being two-fold greater [ 25]. Allowing for greater oropharangeal deposition of budesonide with a daily (25% vs 55% suppression), whereas with budesonide 800 mg twice daily this effect was much less turbuhaler than with a nebuhaler, these data suggest an almost two-fold greater lung delivery of budesonide pronounced (26% vs 34% suppression) [32 ].…”
Section: Introductionmentioning
confidence: 78%
“…The only significant difference was an increased need for β 2 -agonist as rescue medication in the pMDI plus Nebuhaler® group. The effect data must be compared to plasma concentrations of the drug after inhalation from a pMDI plus Nebuhaler® or Turbuhaler®, which showed that Turbuhaler® gave rise to twice the plasma level of drug as compared with pMDI plus Nebuhaler® [106].…”
Section: Budesonidementioning
confidence: 99%
“…A inspiração deve ser rápida e intensa -alto fluxo 81 : em geral são necessários 1 a 2 l/seg (60 a 120 l/min) de fluxo inspiratório para produzir efeito adequado (82); com o Turbuhaler, 0,5 l/seg é suficiente 2,83 , mas se o fluxo inspiratório for maior, de 1 l/seg, os efeitos broncodilatadores serão maiores 84 , refletindo uma melhor deposição pul-monar. Até um certo limite, o aumento do fluxo inspirató-rio aumenta o número de partículas respiráveis, ao contrá-rio do que ocorre com os inaladores pressurizados e dosimetrados 10 .…”
Section: Aerossolterapia Na Asma Da Criança -Souza Lsfunclassified
“…A inalação de aerossol gerado por inalador de pó se acompanha de uma significativa deposição de partículas na orofaringe: com o Turbuhaler, cerca de 57% depositam-se na orofaringe 18 e perdem-se na peça bucal em torno de 24% do aerossol gerado 18 , enquanto que, em média, 17% são depositados nos pulmões e 2% retornam com o ar expirado 18 . Por não ser possível usar-se espaçador acoplado aos inaladores de pó, nada se pode fazer para reduzir a taxa de deposição de droga na orofaringe, que representa um componente importante na biodisponibilidade sistêmica das drogas inaladas através desses aparelhos 82 .…”
Section: Aerossolterapia Na Asma Da Criança -Souza Lsfunclassified